2020
DOI: 10.47197/retos.v38i38.77614
|View full text |Cite
|
Sign up to set email alerts
|

Exercise programme intervention for persons with motor ataxia (Programa de ejercicios de intervención para personas con ataxia motora)

Abstract: Abstract. Introduction: Ataxia affects the nervous system by decreasing balance and coordination most mostly in the trunk, arms and legs. Physical activity is used to help lowering the symptoms of this disease. Objective: The study objective aims to determine the effects of an exercise program intervention focused on quality of life of this person in terms of body composition, hemodynamic parameters and functional capacity. Methods: A Longitudinal study-case with the exercise sessions performed in a gymnasium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it has been shown that patients' quality of life can be improved by greater mobility in later stages of cerebellar degeneration [30,31]. This study [27] also established the proper level of intervention. Because rehabilitation cannot stop the progression of cerebellar degeneration, this is a significant contribution to the research.…”
Section: Treadmill Training and Overground Walking For Balance And Gaitmentioning
confidence: 62%
See 4 more Smart Citations
“…Additionally, it has been shown that patients' quality of life can be improved by greater mobility in later stages of cerebellar degeneration [30,31]. This study [27] also established the proper level of intervention. Because rehabilitation cannot stop the progression of cerebellar degeneration, this is a significant contribution to the research.…”
Section: Treadmill Training and Overground Walking For Balance And Gaitmentioning
confidence: 62%
“…The longitudinal case study by Honorio et al might lend support to earlier case studies that advocated for frequent and intense training [27]. Additionally, Milne et al's systematic review study validates and supports that exercise therapies such as coordination and balance training, balance exercises, respiratory muscle training, and treadmill training can improve the participants' quality of life [33].…”
Section: Locomotor Training Using a Treadmill/intensive Exercisesmentioning
confidence: 69%
See 3 more Smart Citations